1995
DOI: 10.1007/bf00010292
|View full text |Cite
|
Sign up to set email alerts
|

Studies of two Frankia strains isolated from Trevoa trinervis Miers

Abstract: The Frankia strains TtI 11 and TtI 12 isolated from T. trinervis Miers were characterized regarding their carbon source utilization, intrinsic antibiotic resistance, infectivity, and effectivity on the original host. Both strains grew on BAP medium supplemented with glucose, maltose, and sucrose, but differed in their ability to use other carbon sources such as propionate, pyruvate, acetate, succinate, citrate, and mannitol.The isolates were sensitive to five of the twelve antibiotics tested at 1 #g mL-1 conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…These results are in agreement with the findings of Carrasco et al (1995) and Louis et al (1999). They found that all the strains demonstrated sensitivity to some antibiotics.…”
Section: Intrinsic Antibiotic Resistance (Iar)supporting
confidence: 94%
See 1 more Smart Citation
“…These results are in agreement with the findings of Carrasco et al (1995) and Louis et al (1999). They found that all the strains demonstrated sensitivity to some antibiotics.…”
Section: Intrinsic Antibiotic Resistance (Iar)supporting
confidence: 94%
“…Generally, Kafr El-Sheikh isolates showed the highest utilization of the used carbon. The obtained results are in agreement with findings of Benson & Schultz (1990) and Carrasco et al (1995) who found that the utilization of carbon sources by Frankia strains was related to the genomic species that infect the members of the Elaeagnacease and Casuarinaceae, these strains grown on sugars and organic acids.…”
Section: Utilization Of Various Carbon Sourcessupporting
confidence: 92%
“…In general, Frankia strains are sensitive to antibiotics (Carú 1993;Tisa et al 1999;Carrasco et al 1995, Dobritsa 1998. Nine Frankia strains isolated from four Rhamnaceae species were sensitive to ampicillin, penicillin G, rifampicin, chloramphenicol, erythromycin and kanamycin (Carú 1993).…”
Section: Response To Other Chemical and Organic Stressorsmentioning
confidence: 99%
“…Nine Frankia strains isolated from four Rhamnaceae species were sensitive to ampicillin, penicillin G, rifampicin, chloramphenicol, erythromycin and kanamycin (Carú 1993). Frankia strains Ttl11 and Ttl12, isolated from the same plant family are sensitive to rifampicin, chloramphenicol and erythromycin at 1 μg mL −1 (Carrasco et al 1995). In liquid BAP medium, Alnus accuminata isolates AacI and AacIII are sensitive to oleandomycin, erythromycin, kanamycin, penicillin G, streptomycin and chloramphenicol at 1 μg mL −1 (Carú et al 2000).…”
Section: Response To Other Chemical and Organic Stressorsmentioning
confidence: 99%
“…Six isolates used in this study (ChI5, Ds12B, DtI2, ReI6, TqI15, and TtI1) have been phenotypically characterized and differ in some traits, such as physiology, sporulation qualities, resistance to antibiotics, and others (6,8,9,11). Despite having similar 16S rDNA sequences, strain ReI6 grows well on sucrose, whereas TtI1 grows better with pyruvate than with sucrose (6). Also, the strains exhibit some polymorphism in their electrophoretic patterns of esterases, diaphorase, and malate dehydrogenase (unpublished).…”
mentioning
confidence: 99%